Risk of neonatal hyperbilirubinemia in babies born to ‘O’ positive mothers: A prospective cohort study - Kalakheti, BK; Singh, R; Bhatta, NK; Karki, A; Baral, N (Kathmandu University Medical Journal, 2009)
Introduction: Hyperbilirubinemia in a neonate is one of the most common problems that may occur in 60-70 % of term and 80% of preterm babies. It is known to be associated with significant morbidity like neonatal bilirubin encephalopathy and even death. Clinically, and almost exclusively ABO incompatibility occur in ‘A’ and ‘B’ blood group babies of O ‘+ve’ mothers. These babies are reported to be at high risk of severe hyperbilirubinemia (serum bilirubin level more than 16 mg/dl). Objectives: To find out the incidence of hyperbilirubinemia in babies born to ‘O’ positive mothers. To estimate the risk of ABO incompatibility in babies born to ‘O’ positive mothers. Materials and methods: A prospective cohort study conducted in B. P. Koirala institute of Health Science (Department of Pediatrics and Dept. of Gynae and Obstetric) from July 2002 to June 2003. A total of 199 women having ‘O’ positive blood group admitted to the Department of Gynae and Obstetric were included in the study. A piloted proforma was used to collect information. The blood group of neonates was tested by tile and slide method and serum bilirubin was estimated by diazo method in the Central Laboratory Services and Emergency laboratory of BPKIHS. The data was observed and analysis was carried out using statistical software SPSS-10. Results: Total 37 (18.5%) babies had developed hyperbilirubinemia and among them 14 (38%) were from group of babies having ‘O’ Positive blood group and 23 (62%) were from group of babies having other than ‘O’ Positive blood group. There was 2.6 times higher chance of having hyperbilirubinemia in the babies with ABO incompatibility than ‘O’ Positive babies after adjusting other significant variables. Conclusion: Among different significantly associated variables, ABO incompatibility was found to be a major risk factor for neonatal hyperbilirubinemia.It was seen that neonate with ABO incompatibility had two times higher chances of having hyperbilirubinemia than those babies with O ‘+ve’ blood group. This finding in BPKIHS suggests that there is a need of screening cord blood bilirubin and continuous monitoring of bilirubin level in the hospital especially among ABO incompatible neonates. Key words: Hyperbilirubinemia, Neonatal Jaundice, ABO-incompatibility doi: 10.3126/kumj.v7i1.1758 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 11-15